Impact of dental caries on quality of life of adolescents according to access to oral health services: a cross sectional study - Angela Xavier; Érica Silva de Carvalho; Roosevelt da Silva Bastos; Magali de Lourdes Caldana; Patrícia Ribeiro Mattar Damiance; José Roberto de Magalhães Bastos (Universidade Estadual de Campinas, 2016)
Aim: This study presents the prevalence of dental caries and its relation to the quality of life of adolescents according to the access to dental health services. Methods: Two hundred and fifty-six adolescents between 15 and 19 years of age participated in the study; they were all enrolled in public schools in a countryside municipality of the São Paulo State. Data related to dental caries were evaluated by the DMFT Index, and OHIP-14 was used for evaluating the quality of life. Mann Whitney and Spearmann correlation tests were also used (p<0.05). Results: A DMFT of 3.09 (±3.30) was found with a higher prevalence among the adolescents who used public dental services (3.43±3.34) compared with those who used private services (2.94±3.28). A statistically significant relationship between the decay component of DMFT with physical pain (0.020), physical disability (0.002) and quality of life (0.017) was verified. Conclusions: A low prevalence of dental caries was observed, and it was higher in adolescents who used public oral health services rather than private ones, evidencing the low influence of oral health on the quality of life of the participants.